LAYANAN BIMBINGAN KELOMPOK MENGGUNAKAN TEKNIK PROBLEM SOLVING UNTUK MENINGKATKAN SIKAP TANGGUNG JAWAB SISWA KELAS VIII SMPN 2 BATUJAJAR - Nursyamsyiah, Niken Fazri; Wikanengsih; Tuti Alawiyah (IKIP Siliwangi, 2024)
This study was conducted on students of Class VIII, SMPN 2 Batujajar Teaching Year 2022–2023. This study aims to improve students' attitudes of responsibility through group instruction services using problem solving techniques among students in Grade VIII, SMPN2, Batujajar. The method used in research is a mix method, or a combination method between quantitative and qualitative research. A sequential explanatory model is a method that precedes quantitative research and is followed by qualitative research. The data gathering technique used for quantitative research involves using a spread in the form of an angket that has been validated by experts. For the collection of qualitative data using the observation guidelines and interviews with the BK teacher and four students in the 8th grade.Research subjects have a total of 21 students in the experimental class and 21 students in the control class. The results of this study showed that group guidance services with problem solving techniques to improve the attitude of responsibility of students of class VIII SMPN 2 Batujajar have been implemented well.According to the results of the N-Gain test score calculation, the average N-Win score for the experimental class is 68, 1304, or 68% of the students are in the